Air staging combustion and emission from oil burner - Kamarudin, Kamarul-Azhar (2004)
Emissions from combustion of liquid fuel tend to cause an effect to the environment. The formation of pollutant such as NOx, CO, C02 and SOx were hazardous and affect the green house environment. There are many methods in reducing the composition of the pollutant. As the method of reduction becoming more effective, the cost of such technology increases. In this study, air is used as the medium in reduction of the pollutant due to the ease of handling and availability. Airflow rate at 100 l/min is supply within the range of 600 to 1200 0c. At this range, the temperature window created. Air is injected at distance of 900mm from the flame. Results taken from equivalent ratio, which calculated from fuel and airflow rate. At a fix flow rate of fuel and variation of air create a fuel rich, fuel lean and stoichiometric conditions. Combustion efficiency for the combustor is measured versus the equivalent ratio to determine the effectiveness of the air injected to reduce the pollutants. As the results, the reduction of the pollutant relates with the combustion efficiency is measured and analyzed from air staging process.